Efficient biocontrol of Spodoptera littoralis by Aspergillus nidulans, an endophyte of Lantana camara. Issue 4 (24th September 2021) - El-Sayed, Ashraf S.A.; Moustafa, Ahmed H.; El-Sheikh, Aly A.; Rady, Amgad M.; Fathy, Nahla A.M.; Hussein, Hussein A.; Enan, Gamal; Yassin, Marwa A.
Abstract: Spodoptera littoralis has been recognized as a very destructive polyphagous insect, thus, searching for novel bioagents is the current challenge. Endophytic fungi have been recognized as repertoire for bioactive compounds. Thus, the objective of this work was to isolate endophytic fungi inhabiting Lantana camara and evaluating their insecticidal activity against S. littoralis. Aspergillus nidulans, an endophyte of L. camara, displayed a significant larvicidal activity towards 2 nd larval instar of S. littoralis . The morphological identity of A. nidulans has been confirmed from the molecular sequence of ITS region, with genbank accession # MK367603 and deposition # AUMC 14095. The bioactive metabolites of A. nidulans were extracted with EtOAc and DCM and their bioactivity towards S. littoralis was assessed. The values of LC50 were 22.6 and 34.4 µg/mL for dichloromethane and ethylacetate extract, respectively after 18 days of treatment. The chemical identity of insecticidally active compounds was resolved by GC-MS analysis, revealing the presence of major compounds namely 1-docosanol and 1-octadecanol on the EtOAc extract, while cis-9-hexadecenoic acid, and 1-octadecanol were found in the DCM extract. These results indicate that this endophytic fungus could be a potential source for bioactive metabolites and can be used in integrated pest management and other important applications.